THE ROLE OF EMOTIONAL SATISFACTION IN SERVICE ENCOUNTER FOR DEPARTMENT STORES IN JAKARTA - Theresia Tanihaha (Bina Nusantara University, 2009)
The paper examined the role of emotional satisfaction in service encounters. Specifically, this study seeks to investigate the relationship between emotional satisfaction and key concepts such as service quality, customer loyalty, and relationship quality and clarify the role of emotional satisfaction in predicting customer loyalty and relationship quality. In doing so, this study used data from sample survey of 320 Jakarta retail customers concerning their evaluation of shopping experience to address the issue. Descriptive analysis, mean value analysis, independent t-test, ANOVA, and linear regressions were used in analyzing the data. The results showed that service quality was positively associated with emotional satisfaction; emotional satisfaction was positively associated with both customer loyalty and relationship quality. Further analysis revealed that customer’s feeling of being to be pleased is an important indicator of the overall service experience and relationship quality. This study implied that managers of department stores in Jakarta needed to focus on improving and maintaining service quality and enhance the shopping experience such that it resulted in the feeling of being pleased.